Diagnosis and assessment of neuropathic pain through questionnaires. Issue 5 (May 2018) - Attal, Nadine; Bouhassira, Didier; Baron, Ralf
Summary: Neuropathic pain—pain caused by a lesion or disease of the somatosensory nervous system—is underdiagnosed and difficult to treat. However, development of easy-to-use questionnaires based mainly on self-reports of symptoms has improved diagnosis and management. Two types of questionnaires (screening and assessment) have been validated, and rapidly translated and revalidated in several languages, probably because of their simplicity. Screening questionnaires help clinicians to identify neuropathic pain easily, particularly in patients with complex medical conditions (eg, spinal cord injury). Their use in large-scale epidemiological studies has provided estimates of the prevalence of neuropathic pain and identified risk factors for neuropathic pain in the general population and in disorders such as diabetes. Assessment questionnaires measure neuropathic symptoms and have been used to create phenotypic profiles of patients in various neuropathic conditions. These profiles can predict treatment outcomes, and thus enable a personalised therapeutic approach. The dissemination of these questionnaires in different countries should further improve diagnosis and management worldwide and advance knowledge on the mechanisms of neuropathic pain.